2018
DOI: 10.2196/11006
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Patient Interest in the Use of New Technologies to Manage Their Disease: Cross-Sectional Survey

Abstract: BackgroundInformation and communication technologies (ICTs) in oncology can revolutionize the medical care of cancer patients. ICTs can promote patients’ empowerment and real-time disease monitoring. There is limited information about the impact of ICTs in cancer patients or their level of interest in using these tools for greater management of their condition.ObjectiveThis study aimed to understand the ICT usage profile in hematology-oncology patients to identify their needs and determine their level of inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 18 publications
4
41
1
1
Order By: Relevance
“…A recently published review showed that only 6 (15%) of 40 electronic systems incorporated this modality [ 10 ]. Although several studies have shown that patients highly value this function, its complexity and maintenance limit its usability [ 10 , 24 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review showed that only 6 (15%) of 40 electronic systems incorporated this modality [ 10 ]. Although several studies have shown that patients highly value this function, its complexity and maintenance limit its usability [ 10 , 24 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, there were more than 300,000 mHealth apps, and this number tends to grow by 25% every year. In 2018, 52% of smartphone users collected health-related information on their smartphones, and 60% of smartphone users downloaded health-related apps [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cancer patient participants in the study were particularly interested in receiving tailored information based on their ePRO scores, and some participants commented that they had wondered why they had not previously received this information. This interest highlighted the commonly held desire of patients to receive personalized feedback and instruction on self-management practices through web-based and eHealth platforms [ 30 - 32 ]. My NM Care Corner was generally perceived as filling a gap in the support they received through the provision of tailored information.…”
Section: Discussionmentioning
confidence: 99%